A phase II study of sunitinib as a second-line treatment in advanced biliary tract carcinoma: A multicentre, multinational study - Jun Ho Yi (2018)
Background: Biliary tract carcinoma (BTC) is rare in the West, but not uncommon in Asia and is a highly fatal malignancy. VEGF expression is related with poor outcome in patients with BTC. Therefore, we conducted a phase II study to evaluate the efficacy and safety of sunitinib as second-line treatment. Methods: This was a prospective, single-arm, multicentre, multinational study. Patients with unresectable, metastatic BTC who progressed after first-line chemotherapy were eligible. Sunitinib was administered at 37.5mg once daily continuously with 4-week cycle. The primary end point was the time to progression (TTP). Results: Between May 2009 and October 2010, a total of 56 patients were enrolled from three countries. The median age was 55 years (range 38-75) and male to female ratio was 37:19. Median TTP was 1.7 months (95% confidence interval (CI) 1.0-2.4). The objective response rate was 8.9% (5 partial response) and disease control rate was 50.0%. (23 stable disease) Grade 3-4 toxicities were observed in 46.4% of the patients with neutropenia and thrombocytopenia being the most frequent (21.4%). Conclusions: This phase II study suggests that sunitinib monotherapy demonstrated marginal efficacy in metastatic BTC patients although toxicity should be concerned in Asian population. © 2011 Elsevier Ltd. All rights reserved.